Prospective study of bacteraemia in acute haemorrhagic diarrhoea syndrome in dogs. (21st March 2015) - Unterer, S.; Lechner, E.; Mueller, R. S.; Wolf, G.; Straubinger, R. K.; Schulz, B. S.; Hartmann, K.
Abstract : In dogs with idiopathic acute haemorrhagic diarrhoea syndrome (AHDS), a serious loss of intestinal mucosal barrier integrity occurs. However, the incidence of bacterial translocation in dogs with idiopathic AHDS is not known. Thus, the objectives of this prospective study were to identify the incidence of bacteraemia, to evaluate the frequency of septic events and the influence of bacteraemia on various clinical and laboratory parameters, duration of hospitalisation and survival of dogs with idiopathic AHDS. The study included 87 dogs with idiopathic AHDS. Twenty‐one healthy dogs served as control group. To evaluate clinical significance of bacterial translocation, blood culture results were compared between patients and controls. Clinical and laboratory parameters were compared between patients with positive and negative blood cultures. There was no significant difference in either incidence of bacteraemia between patients with idiopathic AHDS (11 per cent) and controls (14 per cent) or in severity of clinical signs, laboratory parameters, duration of hospitalisation or mortality between blood culture‐positive and culture‐negative dogs with idiopathic AHDS. The results of this study suggest that the incidence of bacteraemia in dogs with idiopathic AHDS is low and not different from that of healthy control dogs. Bacteraemia does not influence the clinical course or survival and thus antibiotic treatment is not indicated to prevent sepsis.